Characterization of IncHI1B Plasmids Encoding Efflux Pump TmexCD2-ToprJ2 in Carbapenem-Resistant Klebsiella variicola, Klebsiella quasipneumoniae, and Klebsiella michiganensis Strains - Wang, Yujiao; Zhu, Bo; Liu, Min; Dong, Xiutao; Ma, Jianping; Li, Xiaofeng; Cheng, Fang; Guo, Jianzhuang; Lu, Sumei; Wan, Furong; Hao, Yingying; Ma, Wanshan; et al. (Frontiers in Microbiology, 2021)
Tigecycline serves as one of the last-resort antibiotics to treat severe infections caused by carbapenem-resistant Enterobacterales. Recently, a novel plasmid-mediated resistance-nodulation-division (RND)-type efflux pump gene cluster, TMexCD1-TOprJ1, and its variants, TMexCD2-TOprJ2 and TMexCD3-TOprJ3, encoding tetracyclines and tigecycline resistance, were revealed. In this study, we reported three TMexCD2-TOprJ2-harboring Klebsiella species strains, collected from two teaching tertiary hospitals in China, including one K. quasipneumoniae, one K. variicola and one K. michiganensis. The three strains were characterized by antimicrobial susceptibility testing (AST), conjugation assay, WGS and bioinformatics analysis. AST showed that K. variicola and K. quasipneumoniae strains were resistant to tigecycline with MIC values of 4 μg/ml, whereas the K. michiganensis was susceptible to tigecycline with an MIC value of 1 μg/ml. The TMexCD2-TOprJ2 clusters were located on three similar IncHI1B plasmids, of which two co-harbored the metallo-β-lactamase gene blaNDM-1. Conjugation experiments showed that all three plasmids were capable of self-transfer via conjugation. Our results showed that this novel plasmid-mediated tigecycline resistance mechanism TMexCD2-TOprJ2 has spread into different Klebsiella species, and clinical susceptibility testing may fail to detect. Its further spread into other clinical high-risk Klebsiella clones will likely exacerbate the antimicrobial resistance crisis. A close monitoring of the dissemination of TMexCD-TOprJ encoding resistance should be considered.